Macroeconomics an introduction - Thomas, Alex M. (Cambridge, [England] Cambridge University Press, 2021)
"This book introduces the reader to the subject matter of economics. It explores the topics of activity levels, employment, money, inflation, and economic growth by providing the reader with new research in these fields and also by linking theory with Indian economic policies. It raises thought-provoking questions about the nature of assumptions, the logic, limits, and scope of theory, the theory-policy interface, theory-data gaps, and the politics behind the evolution and nature of economic thought. The aim of the book is to arm students with a strong and practical learning of the subject while enabling them to identify credible sources of information and the ability to evaluate contending arguments, perspectives, and standpoints"--Provided by publisher.
Reprint 2022.
Includes bibliographical references and index.
Keywords: Macroeconomics